The relationship between isometric mid-thigh pull variables and athletic performance measures: empirical study of English professional soccer players and meta-analysis of extant literature - Mason, L.; Kirkland, A.; Steele, J.; Wright, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: There is currently limited evidence available to support the use of the isometric mid-thigh pull (IMTP) within professional soccer. The aim of this study was to analyze the association between IMTP variables, with common markers of athletic performance capability. METHODS: Eleven professional development soccer players (age: 20±2 years, stature: 1.82±0.10 m, mass: 76.4±12.8 kg) performed IMTP, 5 m and 10 m accelerations, maximal sprint speed (MSS), countermovement jump (CMJ), and the 505 change of direction test (COD). RESULTS: Relative and absolute peak force (PF) and force at 50, 100, 150 and 200 ms values were measured during the IMTP. Relative F150, F200, PF displayed large to very large correlations with MSS (r=0.51, r=0.66, and r=0.76 respectively), while absolute PF also displayed a large correlation with MSS (r=0.57). Relative and absolute PF showed large correlations with CMJ height (r=0.54 and r=0.55 respectively). Relative F150 and F200 highlighted large correlations with COD ability (r=-0.68 and r=-0.60 respectively). Relative F200 and PF had a large negative correlation with 10 m acceleration (r=-0.55 and r=-0.53 respectively). CONCLUSIONS: This study provides an important contribution to knowledge within the area of IMTP testing in professional soccer by evidencing the prominence of the isometric force generating capacity as an underpinning factor in relation to athletic capability.